PENGARUH NAIK TURUN BANGKU DAN NAIK TURUN TANGGA TERHADAP PENINGKATAN KEBUGARAN JASMANI - Agatha Dian Anggraeni; Ade Jubaedi; Wiyono Wiyono (JUPE (Jurnal Penjaskesrek), 2014)
This study aims to determine the ratio between the exercises up and down the bench and climbed down the stairs to the improvement of physical fitness class X in SMA Negeri 1 Seputih Agung . The population in this study were students of SMA Negeri 1 Seputih Agung with the sample used in this study were 36 students using test techniques. The method used in this study is the experimental method to the study design